Performance Analysis of Turbo Charger in Two Wheeler Engine - Vanangamudi, S.; Thamotharan, C.; Naveenchandran, P.; Prabhakar, S.; Anbazhagan, R. (International Journal of Psychosocial Rehabilitation, 2018)
The progress of automobiles for transportation has been intimately associated with the progress of civilization. The automobile of today is the result of the accumulation of many years of pioneering research and development. An attempt has been made in this project, the exhaust gas is used to rotate the turbine , which in turn to rotates the impeller connected it . Our fore most aim in selecting this project is to use efficiency turbo charging. It is also good with regard to economical considerations and engine efficiency.